The Neonatal Fc Receptor (FcRn): A Misnomer? - Pyzik, Michal; Sand, Kine M. K.; Hubbard, Jonathan J.; Andersen, Jan Terje; Sandlie, Inger; Blumberg, Richard S. (Frontiers in Immunology, 2019)
Antibodies are essential components of an adaptive immune response. Immunoglobulin G (IgG) is the most common type of antibody found in circulation and extracellular fluids. Although IgG alone can directly protect the body from infection through the activities of its antigen binding region, the majority of IgG immune functions are mediated via proteins and receptors expressed by specialized cell subsets that bind to the fragment crystallizable (Fc) region of IgG. Fc gamma () receptors (FcR) belong to a broad family of proteins that presently include classical membrane-bound surface receptors as well as atypical intracellular receptors and cytoplasmic glycoproteins. Among the atypical FcRs, the neonatal Fc receptor (FcRn) has increasingly gained notoriety given its intimate influence on IgG biology and its ability to also bind to albumin. FcRn functions as a recycling or transcytosis receptor that is responsible for maintaining IgG and albumin in the circulation, and bidirectionally transporting these two ligands across polarized cellular barriers. More recently, it has been appreciated that FcRn acts as an immune receptor by interacting with and facilitating antigen presentation of peptides derived from IgG immune complexes (IC). Here we review FcRn biology and focus on newer advances including how emerging FcRn-targeted therapies may affect the immune responses to IgG and IgG IC.